2015
DOI: 10.1186/s12933-015-0252-x
|View full text |Cite
|
Sign up to set email alerts
|

MuRF2 regulates PPARγ1 activity to protect against diabetic cardiomyopathy and enhance weight gain induced by a high fat diet

Abstract: BackgroundIn diabetes mellitus the morbidity and mortality of cardiovascular disease is increased and represents an important independent mechanism by which heart disease is exacerbated. The pathogenesis of diabetic cardiomyopathy involves the enhanced activation of PPAR transcription factors, including PPARα, and to a lesser degree PPARβ and PPARγ1. How these transcription factors are regulated in the heart is largely unknown. Recent studies have described post-translational ubiquitination of PPARs as ways in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 112 publications
3
37
0
Order By: Relevance
“…Lange et al [10] found that MuRF2 could translocate into nuclei and regulate the activity of the nuclear transcription factor SRF in myocytes. Coincidentally, another study performed by He et al [30] identified that MuRF2 could also regulate the nuclear transcription factor PPAR-c1 in cardiomyocytes. Our study found that MuRF2 translocated into nuclei in LPS-stimulated RAW264.7 cells compared with control groups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lange et al [10] found that MuRF2 could translocate into nuclei and regulate the activity of the nuclear transcription factor SRF in myocytes. Coincidentally, another study performed by He et al [30] identified that MuRF2 could also regulate the nuclear transcription factor PPAR-c1 in cardiomyocytes. Our study found that MuRF2 translocated into nuclei in LPS-stimulated RAW264.7 cells compared with control groups.…”
Section: Discussionmentioning
confidence: 96%
“…Coincidentally, another study performed by He et al . identified that MuRF2 could also regulate the nuclear transcription factor PPAR‐γ1 in cardiomyocytes. Our study found that MuRF2 translocated into nuclei in LPS‐stimulated RAW264.7 cells compared with control groups.…”
Section: Discussionmentioning
confidence: 99%
“…5D, blue box). While the identification of a mono-ubiquitinated TRα was not achieved, we did identify the common dichotomy competing mono- and poly-ubiquitin for substrates, known to be dependent on the types of E2 present and ratios of E3 to substrates (He et al 2015, Kim et al 2007, Lai et al 2001). …”
Section: Resultsmentioning
confidence: 89%
“…By mono-ubiquitinating one to three lysines adjacent to a newly identified nuclear export sequence in PPARα, MuRF1 inhibited PPARα-regulated fatty acid oxidation both in vitro and in vivo (Rodriguez et al 2015). Complementary to these studies, the closely related muscle-specific ubiquitin ligase MuRF2 inhibited PPARγ 1 (He et al 2015), whereas MuRF3 inhibited PPARβ activity in vivo by mono-ubiquitination (Quintana et al 2015). In this study, we identify the cardiac ubiquitin ligase MuRF1 as an inhibitor of T3-induced physiological cardiac hypertrophy in vivo .…”
Section: Introductionmentioning
confidence: 90%
“…fatty acid metabolism) 146–148 . Complementary to this, cardiac MuRF2 and MuRF3 family members attenuate PPARβ/δ and/or PPARγ1 activities to protect against PPAR-ligand induced cardiomyopathy seen in high fat diet challenges in vivo 149,150 .…”
Section: Muscle-specific Ubiquitin Ligases: Regulation Of Cardiac Masmentioning
confidence: 95%